2008
DOI: 10.1016/j.jvs.2008.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Combined endovenous laser therapy and microphlebectomy in the treatment of varicose veins: Efficacy and complications of a large single-center experience

Abstract: EVLT of all sites of superficial axial reflux above and below the knee and microphlebectomy demonstrated that the combined approach is safe and effective at eliminating reflux, affording symptomatic relief, and healing ulcers. It offers the additional advantage of resolving varicose veins and its cause in just one visit, leading to immediate better cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
46
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 18 publications
2
46
1
2
Order By: Relevance
“…Other authors have suggested that BMI Ͼ30 kg/m 2 is a risk factor for recanalization. 13 In our study, the BMI was Ͼ30 kg/m 2 in 6 of 13 patients (46%) in the anatomic failure group compared with 32 of the 105 patients (30%) who had successful outcomes. There was no significant difference in QOL over time due to BMI (P Ͼ .5).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Other authors have suggested that BMI Ͼ30 kg/m 2 is a risk factor for recanalization. 13 In our study, the BMI was Ͼ30 kg/m 2 in 6 of 13 patients (46%) in the anatomic failure group compared with 32 of the 105 patients (30%) who had successful outcomes. There was no significant difference in QOL over time due to BMI (P Ͼ .5).…”
Section: Discussionmentioning
confidence: 51%
“…11,[12][13][14] It is not clear at what BMI threshold recanalization risk begins; however, the larger the leg, the more difficult it is to achieve adequate perioperative vein compression with tumescent anesthesia, compression wraps, and stockings. Other authors have suggested that BMI Ͼ30 kg/m 2 is a risk factor for recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In a recent report from the Michigan Venous Study Group on 443 limbs, 24 however, EVLA alone in 308 limbs (69.5%) and combined with phlebectomy or perforator ligation in 135 limbs (30.5%) had an overall 7.9% incidence of AT events (0.7% true DVTs and 7.2% SFJ thrombus extensions). The true DVT rate was 2.2% for combined EVLA/venous operations and 0% for isolated EVLA (P ϭ .028); the rate of SFJ thrombus extension was 5.9% for combined EVLA/ venous operations vs 7.8% for isolated EVLA (P ϭ .554).…”
Section: Discussionmentioning
confidence: 99%
“…Among many other advantages, it is now appreciated from recent studies on endovascular saphenous vein treatment that the tumescent technique allows not only for the development of tissue plane dissection, but also hygroscopic external tissue pressure on vasculature, in addition to the effect of the adrenalin in the tumescent formula 3,4 …”
mentioning
confidence: 99%